Alkali Metal (Li, Na, K, Rb, Cs) Mediation in Magnesium Hexamethyldisilazide [Mg(HMDS)2] Catalysed Transfer Hydrogenation of Alkenes. Issue 10 (7th April 2021) - Gentner, Thomas X.; Kennedy, Alan R.; Hevia, Eva; Mulvey, Robert E.
Abstract: Though s ‐block organometallics are indispensable tools in synthetic chemistry, their impact in homogeneous catalysis has been small compared to that for transition metals. Surprisingly, however, Group 1 and 2 compounds have recently been utilised in hydroelementation catalysis. For example, transfer hydrogenation of alkenes to alkanes has been catalysed by Group 2 (Ca, Sr, Ba) bis‐hexamethyldisilazides (HMDS), though reactions failed with magnesium. Stimulated by the knowledge that alkali metals can mediate applications of other compounds, this study reports successful catalytic transfer hydrogenation of alkenes with magnesium bis‐hexamethyldisilazide when combined with alkali metals in heterobimetallic complexes. By screening all Group 1 metals (Li−Cs), the efficiency of these catalyses gives an indication of the relative power of the synergistic effect exerted on magnesium by the alkali metal. The Cs−Mg partnership shows the best efficiency with styrene, while K−Mg works best with 1, 1‐diphenylethylene. Abstract : Competitive Alkali Metal Mediation : This rare catalytic study of the complete alkali metal (M=Li−Cs) group compares the performance of magnesiates MMg(HMDS)3 in transfer hydrogenation reactions of alkenes using cyclohexadiene as the hydride source to quantify the relative power of alkali metal mediation on Mg(HMDS)2, which on its own is catalytically inert.